2014
DOI: 10.1068/p7637
|View full text |Cite
|
Sign up to set email alerts
|

How Does Vibration Reduce Pain?

Abstract: Cutaneous vibration is able to reduce both clinical and experimental pain, an effect called vibratory analgesia. The traditional explanation for this phenomenon is that it is mediated by lateral inhibition at the segmental (spinal cord) level, in pain-coding cells with center-surround receptive fields. We evaluated this hypothesis by testing for two signs of lateral inhibition-namely (1) an effect of the distance between the noxious and vibratory stimuli and (2) an inhibition-induced shift in the perceived loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
3
41
1
Order By: Relevance
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
“…Combining vibratory stimulation with either electrical or thermal stimulation increases the analgesia effect, probably due to the activation and recruitment of multiple types of receptors [30,31,57]. Vibratory analgesia of 70-80 Hz has been successfully used to reduce pain in various procedures, including IV insertion [59], blood collection [58] and experimentally-induced pain [70]. In a study on patients with temporomandibular disorder, 20-Hz vibration on the cheek reduced pain, but not as much as 100-Hz vibration [62].…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible mechanism to reduce the impact of C-fiber-mediated pain is the application of a vibrotactile stimulus at the site of stimulation. By stimulating large Aβ fibers with a non-noxious vibration, the transmission of pain signals by small Aδ or C-fibers can be reduced through either primary afferent depolarization of large cutaneous fibers (see Whitehorn &Burgess, 1973 andRudomin &Schmidt, 1999 for review), or the activation of inhibitory interneurons (see Gate Control Theory by Melzack & Wall (1965); see also Hollins, McDermott, & Harper (2014) for a review). Previous studies have found that the simultaneous application of vibrotactile stimulation (at frequencies of 50-150 Hz, see Lundeberg, Nordemar, & Ottoson, 1984) directly on, or near, the site of a painful stimulus increases pain tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration has been proposed recently to involve two cortical areas that are primarily involved in coding pain and touch (Hollins, McDermott, & Harper, 2014). Vibration appears to activate analgesic mechanisms which can powerfully inhibit experimental pain.…”
mentioning
confidence: 99%